MODEL FOR FORMING YOUNGER SCHOOL CHILDREN ABILITY TO WORK WITH TEXT IN OUTSTANDING ACTIVITIES - Saydullayeva Feruza Asliddinovna; Raxmonova Laylo Odiljon qizi (Galaxy International Interdisciplinary Research Journal, 2021)
The article describes a model of extracurricular activities for the formation of the ability to work with text in junior schoolchildren. The meaning of each block of the model is disclosed. A program of extracurricular activities for the formation of the ability to work with text in junior schoolchildren is presented